ANALYSIS OF PAPER DEFECT REDUCTION IN PAPER INDUSTRY WITH LEAN SIX SIGMA APPROACH - Fika Aras Ardita dan Sukardi (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT   The high number of the defective product that occur in each company can affects the quality. PT. X is a company engaged in the pulp and paper product. Lean approach does not allow for waste, in this case is defective product. Product defects that often arise in this  industry are holes paper, dirty paper, folded, size variations and foreign contamination. The purpose of this study is to identify the causative factor in the production department of a product defect based on six sigma phase and the solution  that can be taken to reduce the number of defects in the production department based. The phases of six sigma are define, measure, analyze, improvement and control. The results of calculation of the value of sigma of perforated paper for two months was 3.45 and 3.47. Dirty paper has a sigma value of 4.2 and 4.5. The sigma level indicates that the performance of the productionis above average Indonesian company. The costumer complaint coming into the company for  folded paper, size variations and foreign contamination has decreased from 2010 to 2011. But it has not reached the six sigma target. So that, the company  needs to be  improved using the Lean tool that is  Kaizen Blitz.     Keywords : defective product , paper , six sigma, lean, kaizen blitz